Diels–Alder reactions between cyclopentadiene analogs and benzoquinone in water and their application in the synthesis of polycyclic cage compounds. Issue 2 (2nd January 2020) - Shi, Yijun; Liu, Xuejing; Han, Ying; Yan, Peng; Bie, Fusheng; Cao, Han
Abstract : Diels–Alder reactions between cyclopentadiene analogs and p -benzoquinone were explored in water and yielded 83–97% product, higher than the results reported in water with a catalyst or cetrimonium bromide (CTAB) micelles. Abstract : Diels–Alder reactions between cyclopentadiene analogs and p -benzoquinone were explored in water and yielded 83–97% product, higher than the results reported in water with a catalyst or cetrimonium bromide (CTAB) micelles. The novel adduct 10 was synthesized and further used to synthesize the bi-cage hydrocarbon 4, 4′-spirobi[pentacyclo[5.4.0.0 2, 6 .0 3, 10 .0 5, 9 ]undecane], which has a high density (1.2663 g cm −3 ) and a high volumetric heat of combustion (53.353 MJ L −1 ). Four novel bi-cage hydrocarbon compounds were synthesized in water using this method starting from 2, 2′-bi( p -benzoquinone) and cyclopentadiene analogs.